Immediate Clinical Outcome of 600 Cases of Percutaneous Coronary Intervention (PCI) - Uddin, MJ; Hussain, KS; Ali, M; Chowdhury, AHK; Haque, SA; Rahman, MS; Rahman, F; Khan, AR; Saifullah, M; Sarwar, A; et al. (University Heart Journal, 2008)
This is an ongoing study done in National Institute of Cardiovascular Diseases (NICVD) during the period April 2002 to October 2007, few cases were done in Eurobangla Heart Hospital, Lab Aid Cardiac Hospital & National Heart Foundation, SSMC & MH, Metropolitan Medical Center. Total number of study population was 600 with male 550 & female 50. Indication of Percutaneous coronary intervention (PCI) was- Unstable angina (with no prior myocardial infarction) 240 cases, MI inferior (with post Myocardial infarction angina) 204 cases & MI anterior (with post MI angina) 156 cases. The risk factors were Hypertension (HTN) 310 cases (52%), smoking 426 cases (71%), Diabetes Mellitus (DM) 180 cases (30%), Positive family history for ischemic heart diseases (IHD) 120 cases (20%), Hyperlipidemia 150 cases (25%). Total number of target coronary arteries was 760 and total number of lesion was 803 of which780 lesions treated. Distribution of 803 lesions were left anterior descending coronary artery (LAD) 389 (proximal LAD 152, mid LAD 177, distal LAD 60), Right coronary artery (RCA) 230 (proximal 94, mid RCA 93, Distal RCA 26, RCA PD 17), Left circumflex coronary artery (LCX) 137 (proximal LCX 60, mid LCX 54, distal LCX 16, LCX PD 07), diagonal 15, obtuse marginal (OM) 20, ramus intermedius. Angiographic diagnosis of the patients were Single vessel disease 312 (52%), Double vessel disease 156 (26%) & Triple vessel disease 132 (22%). Number of lesions treated were 803 of which 780 lesions was treated. PTCA with stenting done in 725 lesion & 34 lesions treated with plain PTCA. Total occlusion was treated in 85 cases. The native vessel has a mean reference diameter was 3.03 ± 0.61 mm. Residual stenosis after deploying stents was <10%. Our success rate was-angiographic success 96%, procedural success 94% & clinical success 92%. Total mortality was 03. One patient having triple vessel disease died on P the procedure due to sudden cardiac arrest due to asystole, one pt died on the table due to acute closure by thrombus & one patient died on 4th day due to huge retroperitoneal hemorrhage & shock. Sub acute stent thrombosis occurs in 3 cases causing acute myocardial infarction & one case required emergency CABG. Following procedure, in hospital course of the patients were uneventful. All the patients were discharged by three to fourth day of the procedure with improvement of their clinical condition. So the result of our study is good both in plain PTCA group & PTCA + stent group. (University Heart Journal 2007; 3 : 50-56)